Exploring natural variation in duckweed – using genomics and phenotypic approaches - Smith, Kellie E. (2024)
The duckweeds comprise 36 species, containing both the smallest and fastest growing Angiosperms. Their aquatic growth habit and clonal production makes them ideal for phytoremediation and food applications. Duckweed contain ~45% protein by dry weight, high vitamins e.g. carotenoids and minerals including K, P and Fe. However, natural variation in these aspects have not so far been used for selection of species and accession suitability for human consumption or phytoremediation. For existing available duckweed clones domesticated in controlled environments, the original light and water environments are largely unknown. Here, a novel UK cohort with native water and light assessments are used to identify accessions for commercial applications. This work reports species and accession variation in minerals, heavy metals, aroma, metabolites and light responses in controlled environments by combined genotyping and phenotyping. The Lemna genus showed high elemental variation: with submerged Lemna trisulca hyperaccumulating five elements and Lemna yungensis showing variation between accessions. From the novel UK collection, higher Mg was found in Lemna minuta and higher K and As in Lemna japonica, additionally with species inhabiting higher Mg and As water environments respectively. Accessions of these species could be trialed on wastewater to maximise elemental extraction for phytoremediation, however high heavy metal contents represents a challenge for food safety. For consumption, accession and environment were manipulated to maximise growth by increasing light irradiance. Especially suitable were hybrid Lemna japonica accessions originating from low light, which acclimated to artificial high light by fast growth, high photoprotection and increased carotenoids. During glasshouse growth, aroma profiles varied between duckweed species but were comparable to spinach and provisionally acceptable for human consumption. Moving forward, specific functions of duckweed aroma and metabolite compounds in human health should be elucidated. Together, phenotyping, genome sequencing and environmental assessment form a tool to understand natural variation for applications.